Rapidly Progressive Pulmonary Apical Fibrosis and Parenchymal Destruction in a Patient with Ankylosing Spondylitis - Ulusoy, Hasan (Case Rep Rheumatol, 2020)
Pulmonary apical fibrosis is a rare complication of ankylosing spondylitis (AS). The essential characteristics of this lesion are its very slow progression and frequently asymptomatic nature. Herein, we are presenting a patient with AS who rapidly developed pulmonary apical fibrosis in a 3-year period despite decreased musculoskeletal pains. The 60-year-old male applied with complaints of progressively increasing cough in the recent two years, dyspnea, and fatigue. He had no chronic disease except AS. He had no continuous medication except nonsteroid anti-inflammatory drugs for 2-3 days monthly since his musculoskeletal pains decreased in the recent years. His physical examination revealed reduced breath sounds in the upper zones of the right lung. Chest X-ray revealed increased diffuse opacity in the upper zones of the right lung. Thoracic high-resolution computed tomography showed a consolidation accompanied with traction bronchiectases compatible with chronic fibrosis in the upper lobe of the right lung. However, thoracic computed tomography of the patient performed 3 years ago did not reveal pulmonary apical fibrosis and parenchymal destruction. Biopsy revealed no finding of malignancy, granulomatous inflammation, or vasculitis. The results of cultures were negative. So, the patient was diagnosed as pulmonary involvement of AS, which developed in a 3-year period. This case has shown that extra-articular complications may continue to develop in patients with AS even if their musculoskeletal complaints have subsided. So, patients with AS should be followed up regularly with systemic examinations.